A Glimpse of Ibnu Jinni's Biography and Arabic Linguistic Thought - Siregar, Juwairiyah; Nandang Sarip Hidayat; Tatta Herawati Daulae (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2024)
The Arabic language in its development, gave birth to many experts and thinkers who made a major contribution to the science of linguistics. One of the leading linguistic figures is Ibn Jinni. Ibn Jinni made a major contribution to the development of Arabic linguistics. This study aims to examine in depth the biography and Arabic linguistic thought of Ibn Jinni. This research uses the literature study method. This study found that Ibn Jinni was not just a linguist, but a critical thinker who dared to open new paths in the study of Arabic linguistics. Some Arabic linguistic thoughts put forward by Ibn Jinni are the difference between qaul and kalam, the definition of language is thesounds used by a people to express their goals, language must be agreed upon by the language-speaking community so that communication can be communicative, viewing lafazh and meaning as two inseparable elements in the macro linguistic spectrum, no two languages are identical, although there are similarities in words or synonyms, usually one of the words has a higher frequency of use and is the original word of its users.